Contribution of media on knowledge generation about tuberculosis in Palpa district, Nepal - Karki, Deelip Kumar; Singh, Birendra Kumar; Khanal, Pravin Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: Media is the means of communication, as radio, television and newspaper that reach or influence people widely. It is a tool for the transfer of information and ideas to audiences. The media plays the crucial role in instructing, motivating and guiding the public for control of tuberculosis. The objectives of the study were to study the knowledge and the source of information regarding tuberculosis. Methods: A cross sectional study was conducted whereas multistage sampling was adopted. Results: Around half of respondents (46.5%) were 15-24 years of age and 63.9 per cent were female. Overwhelming number of the respondents (95.1%) had radio and more than one fourth (76.4%) had television at home. More than three quarter (88.9%) respondents said droplet infection is the mode of transmission of tuberculosis but 11.1 per cent said sharing common utensil. 97.2 per cent respondents had good behaviour towards TB patient. In respect to knowledge score, 18.1 per cent had high level of knowledge followed by 56.2 per cent had medium and 25.7 per cent had low level. Fifty per cent respondents said television, 46.5 percent said radio were the source of information for tuberculosis. Conclusions: The study found that majority of the respondents had satisfactory knowledge level about tuberculosis. The results exemplify the contribution of media on improving TB related knowledge. Most of the respondents ranked media, i.e., radio and television is the number one source of information.